(untitled) (Journal of Basic and Applied Research in Biomedicine, 2022)
The present study includes detailed aspects of seeds of Lagenaria siceraria (Mol.) Standley used as medicinal plant. The Lagenaria seeds contain steroidal moieties like avenasterol, codisterol, elesterol, isofucasterol, stigmasterol and Legenin, a ribosome inactivating protein(RIP) isolated from seed shows various pharmacological activity. Antioxidants consist a group of vitamins, minerals and enzymes that have health enhancing effects. Antioxidants terminate the chain reactions by removing free radical intermediates before they do harm to our bodies. Antibacterial agents are inhibitory chemicals employed to kill micro-organisms or prevent their growth.Antianxiety agent a pyschotropic medication involves functional category of drugs useful in the treatment of anxiety and able to reduce anxiety at dosage that not cause excessive sedation.The elevated plus maze is a widely used behavioral assay for rodents and it has been validated to assess the anti-anxiety effects of pharmacological agents.An increase in open arm activity reflects anti-anxiety behavior.